Molecular Networking Revealed Unique UV-Absorbing Phospholipids: Favilipids from the Marine Sponge Clathria faviformis - Silvia Scarpato; Roberta Teta; Paola De Cicco; Francesca Borrelli; Joseph R. Pawlik; Valeria Costantino; Alfonso Mangoni (Marine Drugs, 2023)
Analysis of extracts of the marine sponge Clathria faviformis by high-resolution LC-MS2 and molecular networking resulted in the discovery of a new family of potentially UV-protecting phospholipids, the favilipids. One of them, favilipid A (1), was isolated and its structure determined by mass and tandem mass spectrometry, NMR, electronic circular dichroism (ECD), and computational studies. Favilipid A, which has no close analogues among natural products, possesses an unprecedented structure characterized by a 4-aminodihydropiridinium core, resulting in UV-absorbing properties that are very unusual for a phospholipid. Consequently, favilipid A could inspire the development of a new class of molecules to be used as sunscreen ingredients. In addition, favilipid A inhibited by 58–48% three kinases (JAK3, IKKβ, and SYK) involved in the regulation of the immune system, suggesting a potential use for treatment of autoimmune diseases, hematologic cancers, and other inflammatory states.